Blocking Apoptotic Intracellular Signaling Cascades with Cell-Permeable Peptides - Zine, Azel; Uziel, Alain; Beckmann, Jacques; Bonny, Christophe (Current Signal Transduction Therapy, 2007)
Cells are continuously adapting to changes in their environment by activating extracellular stimuli-dependent signal transduction cascades. These cascades, or signaling pathways, culminate both in changes in genes expression and in the functional regulation of pre-existing proteins. The Mitogen-Activated Protein Kinases (MAPKs) constitute a structurally related class of signaling proteins whose distinctive feature is their ability to directly phosphorylate, and thereby modulate, the activity of the transcription factors that are targets of the initial stimuli. The specificity of activation of MAPK signaling modules is determined, at least for an important part, by the specificity of the protein-protein contacts that are required for the propagation of the signal. We will discuss how it is possible to interfere with MAPK signaling by using short cell-permeable peptides able to block, through a competitive mechanisms, relevant protein-protein contacts, and their effects on signaling and cell function.
Keywords: signaling